vanC Cluster of Vancomycin-Resistant Enterococcus gallinarum BM4174 (2000)
Glycopeptide-resistant enterococci of the VanC type synthesize UDP-muramyl-pentapeptide[D-Ser] for cell wall assembly and prevent synthesis of peptidoglycan precursors ending in D-Ala. The vanC cluster of Enterococcus gallinarum BM4174 consists of five genes: vanC-1, vanXYC, vanT, vanRC, and vanSC. Three genes are sufficient for resistance: vanC-1 encodes a ligase that synthesizes the dipeptide D-Ala-D-Ser for addition to UDPMurNAc- tripeptide, vanXYC encodes a D,D-dipeptidase–carboxypeptidase that hydrolyzes D-Ala-D-Ala and removes D-Ala from UDP-MurNAc-pentapeptide[D-Ala], and vanT encodes a membrane-bound serine racemase that provides D-Ser for the synthetic pathway. The three genes are clustered: the start codons of vanXYC and vanT overlap the termination codons of vanC-1 and vanXYC, respectively. Two genes which encode proteins with homology to the VanS-VanR two-component regulatory system were present downstream from the resistance genes. The predicted amino acid sequence of VanRC exhibited 50% identity to VanR and 33% identity to VanRB. VanSC had 40% identity to VanS over a region of 308 amino acids and 24% identity to VanSB over a region of 285 amino acids. All residues with important functions in response regulators and histidine kinases were conserved in VanRC and VanSC, respectively. Induction experiments based on the determination of D,D-carboxypeptidase activity in cytoplasmic extracts confirmed that the genes were expressed constitutively. Using a promoter-probing vector, regions upstream from the resistance and regulatory genes were identified that have promoter activity.